Дуговой реактор переменного тока для синтеза карбидов; Электричество; № 3 - Пак А. Я. Александр Яковлевич; Сперанский М. Ю. Максим Юрьевич; Лавренчук А. А. Антон Анатольевич; Васильева Ю. З. Юлия Захаровна; Некля Ю. А. Юлия Александровна (2024, 2024)
Заглавие с экрана